Partisipasi Masyarakat dalam Mengurangi Risiko Kerusakan Situ-Situ di Kecamatan Cimanggis, Kota Depok - Tiffa Yuki Dewanti; Heru Sri Naryanto (Agency for the Assessment and Application of Technology / Badan Pengkajian dan Penerapan Teknologi (BPPT), 2018)
ABSTRACTDepok City has a function as a water catchment in reducing flooding in Jakarta City and in Depok City itself, the existence of existing sites is very important to be maximized. At present there are only 21 small lake in Depok City whose existence is still maintained. The conditions there each year decrease both in terms of quality and quantity. There are 6 small lake in Cimanggis subdistricts, namely: Situ Gadog, Situ Pedongkelan, Situ Rawa Kalong, Situ Tipar, Situ Jemblung, and Situ Rawa Gede, which as a whole have an area of 32.4 Ha. To maintain small lake preservation in the Cimanggis sub-district, damage risk reduction is urgently needed to sustain the small lake's existence in a sustainable manner. There are 5 variables of community participation in damage risk reduction in Cimanggis sub-district. Five variables to measure the level of community participation are community participation in the form of thoughts, community participation in the form of property, community participation in the form of energy, community participation in the form of skills, and community participation in social forms. Keywords: Community participation, small lake, Cimanggis, damage risk reduction